Pengaruh Diferensiasi Produk, Customer Experience Dan Kualitas Layanan Terhadap Loyalitas Pelanggan Pada Kedai Sayur 24 Malang - Hidayat, Rahmat; Priyono, Achmad Agus; Bastomi, Mohamad (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract The purpose of this study was to determine how "The Influence of Product Differentiation, Customer Experience and Customer Loyalty on Kedai Sayur 24 Malang" The data collection method used purposive sampling, namely sampling from the population based on certain criteria. The data analysis technique used to measure the indicators of questions on the questionnaire is the Likert scale. In this study, the data source used is primary data using the analysis and statistical tools of the IMB SPSS25 program. This study uses a data collection method with a questionnaire and the sample used in this study was 85 respondents. Data analysis methods include quantitative analysis using multiple linear regression techniques and hypothesis testing simultaneously (F test) and partially (t test). The results of this study indicate that simultaneously Product Differentiation, Customer Experience and Quality have a simultaneous influence on Customer Loyalty at Kedai Sayur 24 Malang with a significance level of 0.000 <0.05. Then, partially, the Product Differentiation variable has a significant effect on customer loyalty with a significance level of 0.004 <0.05, while Customer Experience and Service Quality partially have a positive and significant effect on Customer Loyalty with a significance level of 0.021 and 0.000 <0.05. Keywords: Differentiation Product, Customer Experience and customer Loyality on Customer Loyality.